Digital Transformation as a Modern Approach to Financing Startups: Opportunities and Challenges - Nour ElHouda SETIFI; Saida HARKAT (Journal of Excellence for Economics and Management Research, 2026)
This study aimed to highlight the importance of digital transformation in financing startups and to examine the main opportunities and challenges in this field. The study adopted a descriptive approach with an analytical method to present and analyze various digital financing mechanisms, including crowdfunding, peer-to-peer lending, smart financing, and hybrid solutions. It also emphasized their role in enabling startups to overcome the constraints of traditional financing models by providing a flexible and inclusive digital financing framework.The study reached several findings, the most important of which is that digital transformation plays a positive and effective role in financing startups. However, it faces several challenges, most notably legal and regulatory constraints, as well as a lack of financial literacy, which may limit its positive impac